Using wellbeing concept to measure economic and social impacts: A case study of the seaweed processing women's groups in Indonesian villages - Larson, Silva (University of Sunshine Coast, 2019)
Presented by Silva Larson (JCU/USC), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.